Microbiological study of endometritis and its antibiotic spectra in repeat breeder buffaloes - PRAJAPATI, S B; GHODASARA, D J; PRAJAPATI, K S; PUROHIT, J H; JANI, V R (The Indian Journal of Animal Reproduction, 2023)
In the present study, a total of70 cervico vaginal mucus (CVM) samples comprising IO samples from healthy buffaloes and 60 samples from clinical cases of endometritis were screened for bacterial isolates. All IO CVM samples collected from healthy buffaloes did not yield any bacterial culture. CVM samples collected from buffaloes with unhealthy discharge, 54 (90%) CVM samples had bacterial growth comprising 87.04 and 12.96% single and mixed type isolates, respectively. Where as 6 CVM samples did not yield any bacterial culture. The frequency of Staphylococcus spp. was found to be maximum followed by Bacillus spp., E.coli, Proteus spp., Streptococcus spp., Pseudomonas spp. and Salmonella spp. The per cent sensitivity of bacterial isolates was found to be maximum for gentamycin followed by chloramphenicol, enrotloxacin, cephalexin, tetracycline, ampicillin, co-trimoxazole and furazolidone.